(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was carried out with the objective of studying the reproductive performance, blood constituents and economics of rearing Vanaraja birds as influenced by the dietary inclusion of linseed meal. The study was conducted at the poultry unit of the department. A total of 120 female Vanaraja chicks were reared for a period of nine months and were randomly divided into four treatment groups (T1, T2, T3, and T4) of 30 birds, each having five replications per treatment following a randomized block design. They were subjected to four dietary levels of linseed meal, containing 0%, 4%, 8%, and 12%, respectively. The birds were reared under a deep litter system up to 8 weeks of age and thereafter in cages following standard management practices. Initial body weight was recorded at 1 day old, and thereafter it was recorded fortnightly. Feed intake and egg production were recorded daily. The control group had higher egg production, clutch size, and egg weight. Higher yolk weight, albumen weight, and yolk cholesterol were recorded in T3, while group T4 had the maximum HU. The lowest cholesterol and triglycerides were recorded in T4, while the highest HDL and lowest LDL were observed in the control group. The cost of production was highest in T4 and lowest in T2, while higher net profit per bird and net profit per gain were recorded in T3 as compared to the control group.